The bell jar - Plath, Sylvia; Faber & Faber (London : Faber & Faber, 2013)
An autobiographical novel which chronicles the mental breakdown of Esther Greenwood, a gifted young woman working for the summer as a junior editor at a New York magazine in the early 1950s.
Adult.
Adult
Keywords: Depression, Mental -- Fiction; Suicidal behavior -- Fiction; Autobiographical fiction; Depression (Psychology) -- Fiction; Suicide -- Psychological aspects -- Fiction; Autobiographical fiction; Young adult fiction